Hubungan Kreativitas Belajar Dan Gaya Belajar Terhadap Prestasi Belajar Matematika Siswa SMA - Emilianus Jehadus; Eufrasia Jeramat; Elisabeth V. Mbohong (UNIKA SANTU PAULUS RUTENG, 2019)
The study aims to know the (1) a significant correlation in learning creativity and mathematics learning achievement of SMAK XI IIS Setia Bakti Ruteng students in academic year 2019/2020, (2) significant correlation in learning styles and mathematics learning achievement of SMAK XI IIS Setia Bakti Ruteng students in academic year 2019/2020, (3) simultaneous correlationin learning creativity and learning style on the mathematics learning achievemen of SMAK XI IIS Setia Bakti Ruteng students in academic year 2019/2020. The research is an correlation research using the desaign of simple random sampling. The population in all students of class XI IIS SMAK Setia Bakti Ruteng which amounted to 116 people. The number of members of the study sample was 68 people. Data on correlation were collected by descriptions nontest. Data were analyzed using normality test, linearity test, and multicollinearity test were performed. The analysis showed that the data came from populations that were normally distributed, linearly patterned, and not multicollinearly related. Based on the results of data analysis, it was found that the results: (1) a significant correlation of learning creativity and mathematics learning achievement of students with a correlation coefficient of 0.413 and a value of 3.268 > 1.674. The contribution of learning creativity to mathematics learning achievement is 17%. (2) a significant Correlation of learning styles and mathematics learning achievement of students with a correlation coefficient of 0.410 and a value = 3.242 > 1.674. The contribution of learning styles to mathematics learning achievement is 16.8%. (3) a simultaneous correlations in learning creativity and learning style on the mathematics learning achievement of students with a correlation coefficient of 0.546 and a value of 4.700 > 1.674. The contribution of learning creativity and learning styles simultaneously to mathematics learning achievement was 29.8%. Based on these findings it is concluded that there is a relationship between learning creativity and learning style on students' mathematics learning achievement.